Measurement of airborne pollutants - Couling, Suzanne (Butterworth-Heinemann, 1993)
Measurement of Airborne Pollutants stresses the importance of developing air pollution measurements that is central to progress in the formulation of environmental policy, efficient regulation of emissions, and satisfactory control of processes which emit pollutants into the atmosphere. This book is divided into two parts. Part 1 deals with the operational evaluations of emerging techniques for ambient measurements of airborne particles and for low levels of nitrogen dioxide. The calibration techniques for automatic analyses or for gas cylinders obtained from commercial suppliers and fundament.